Effects of Hardness of Counterface on Dry Sliding Wear of Aluminum Matrix Composites against Steels - Toshiro Miyajima (Japanese Society of Tribologists, 2012)
The effect of the hardness of a counterface on the sliding wear behavior of SiC whisker or of SiC particle reinforced aluminum matrix composites (designated as MMCw, MMCp) was investigated by pin-on-disk tests. The counterface materials were 0.45% carbon steel and tool steel with a hardness range (HV=180-1000) obtained by different heat treatment. When the MMCw (Vf=29%) and MMCp (Vf=10%, d=5 µm) pins were rubbed against steel disks, their wear rates took constant values below the hardness of the worn surfaces, but the wear rates varied inversely proportional with increasing hardness of the steel counterface. The wear rates of the steel disks varied inversely with their hardness. On the other hand, when a MMC disk was rubbed against a steel pin, the wear rates of MMCp showed an almost constant value regardless of the counterface hardness. The wear rates of MMCw increased slightly for high hardness of the counterface. The wear rates of the steel counterfaces were remarkably small. These phenomena are discussed depending on the characteristics of worn surfaces, the wear debris and tribo-induced layers on the counterface. The findings obtained in this study contribute to the evaluation of tribological properties of aluminum alloys as well as their matrix composites based on a large variety of experimental data obtained with different wear test methods.